In vitro Characterization of Enterococcus faecium strain LCM08 as a probiotic - Zia, Mariam; Mujahid, Talat Y; Mushtaq , Mamona; Baloch, Muneera Naz (International Journal of Endorsing Health Science Research, 2021)
Background: Under the present situations, where health improvement has become the major concern, food supplements, augmenting health is a matter of interest. Presently, the concept of "functional foods" possessing medicinal attributes has been reborn as probiotics. Acid-tolerant and Gram-positive Lactic acid bacteria (LAB), being the major class of probiotics, possess health-promoting characteristics, provide better health with a robust immune system, and treat various digestive and neurological disorders. Hence, the aim of the present study was the isolation and identification of LAB. Methodology: The LAB were isolated from various sources, including food products and clinical samples. Enterococcus faecium LCM08 being the most potent isolate tested for probiotic traits, including viability under acidic conditions, biological concentrations of bile salts and enzymes. Results: A total of fifty-four strains were isolated, of which 7.2% showed broad-spectrum inhibition against the tested pathogens. Amongst them, Enterococcus faecium LCM08 owing to its broad-spectrum antagonism, when tested for its ability to withstand acidic conditions, displayed 63.58% viability and 72.19% survivability in the presence of bile salts. Moreover, strain sustained in the presence of digestive enzymes including protease (94.65%), trypsin (93.57%) and pancreatin (75.0%) as well as exhibited growth at temperatures ranging between 25˚C and 30˚C where the maximum viable counts recorded as 95% and 96.4%. The strain also produced antimicrobial metabolites at neutral pH. However, elevated temperatures (45˚C-50˚C) inhibited the production of bacteriocin-like inhibitory substances. Conclusion: The preliminary investigations revealed that Enterococcus faecium LCM08 possesses the key attributes pre-requisite for a probiotic candidate.